Sistem monitoring dan otomasi pengontrolan kelembaban media tanam (soil moisture) pada tanaman hidroponik berbasis web - Yuyu Wahyudin; Suryono Suryono; Jatmiko Endro Suseno (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
A web based system design for soil moisture monitoring and automation was conducted on this research. Soil moisture level controlling is highly needed to optimalize plant cultivation result. The system contains of two main parts, a remote terminal unit (RTU) and control terminal unit (CTU). RTU has an ATSAM3X8E microcontroller and a microprocessor used for acquiring and sending soil moisture level to database using internet connection. Using internet as telemetry connection is really efficient and gives many advantages such as measurement could be done in distance and also has realtime result. YL-69 sensor used for soil moisture level measurement gives resistance as the output value. This sensor has a module with a 10K ohm voltage devider resistor. The output sensor value converted into digital value using microcontroler analog to digital converter (ADC). This result then being compared with setpoint value to decide whether the water pump turning on or off. The output sensor value also sent and then saved in online database system through internet connection. A reference was used for determining sensor characterization with the linier formulation y = -0.0245x + 99.9560. The result between sent and received data has no error, so there were no lost or gain data. The response from the sensor tested at setpoint value in 30, 40 and 50 giving errors 3.3%, 6.5% and 10.7% for each value. The system reponse tests showed that in a low setpoint value the system gave a very close value with the setpoint, but as the increasement of the setpoint value, the system got error increasement either. Keywords: database, moisture, microcontroller, soil moisture sensor, telemetry